2020
DOI: 10.1002/oby.23042
|View full text |Cite
|
Sign up to set email alerts
|

Familial Obesity Risk and Current Excess Weight Influence Brain Structure in Adolescents

Abstract: Objective Obesity risk transmits from parents to children. Underlying neural mechanisms were investigated in this study by evaluating influences of familial obesity risk defined by maternal obesity and influences of current overweight on three indices of brain structure in adolescents. Methods In total, 22 lean adolescents with lean mothers (lean low‐risk), 25 lean adolescents with mothers with obesity/overweight (lean high‐risk), and 36 adolescents with obesity/overweight underwent structural MRI scans for es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 44 publications
(73 reference statements)
0
18
0
Order By: Relevance
“…A major theme that emerged from the workshop is that obesity begets obesity (and, by extension, metabolic disease, i.e., T2D begets T2D). Obesity and diabetes can begin in the womb, driven by a complex interplay of genes, behaviors, and environment [ 91 , 92 , 95 97 ]. Brain imaging is helping to elucidate how genes and epigenetic marks influence body weight directly by controlling development of hypothalamic and other brain circuitry, and that of the rest of the body such as the visceral organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major theme that emerged from the workshop is that obesity begets obesity (and, by extension, metabolic disease, i.e., T2D begets T2D). Obesity and diabetes can begin in the womb, driven by a complex interplay of genes, behaviors, and environment [ 91 , 92 , 95 97 ]. Brain imaging is helping to elucidate how genes and epigenetic marks influence body weight directly by controlling development of hypothalamic and other brain circuitry, and that of the rest of the body such as the visceral organs.…”
Section: Discussionmentioning
confidence: 99%
“…She showed that familial obesity risk as reflected by maternal overweight is associated with lower activation to food cues in a self-regulation circuit including the dorsolateral prefrontal cortex, and that food approach behaviors are associated with activation of regions involved in sensing or anticipating reward, including the insular cortex. Subsequent work has further revealed reduced gray matter volume and cortical thickness in regions subserving gustatory processing and self-regulation in association with familial obesity risk [ 95 ]. Key takeaway points include (1) maternal pre-pregnancy obesity impacts connectivity within and between hemispheres and (2) maternal obesity influences the child’s neural self-regulation and reward circuits in response to food cues, as well as regions focused on gustatory processing.…”
Section: Scientific Sessionsmentioning
confidence: 99%
“…Regarding brain morphology, associations between childhood obesity and cortical thickness have been found in diverse brain regions. Many studies have reported association to areas within the frontal lobe [9][10][11][12][13][14] . Yet, other brain regions may also play a role 15 .…”
Section: Main Textmentioning
confidence: 99%
“…Regarding brain morphology, associations between childhood obesity and cortical thickness have been found in diverse brain regions. Many studies have reported association to areas within the frontal lobe (Kim et al, 2020; Prats-Soteras et al, 2020; Rajan et al, 2021; Ross et al, 2015; Saute et al, 2018; Thapaliya et al, 2021), but other brain regions may also play a role (Steegers et al, 2021). In participants with higher obesity, cortical surface area was observed to be increased in the left rostral middle frontal gyrus and the right superior frontal gyrus (Prats-Soteras et al, 2020) while others found cortical volume to be altered in frontal and temporal brain regions (Alosco et al, 2014; Hashimoto et al, 2015; Kennedy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a chronic metabolic disease caused by many factors, which has been listed by the World Health Organization as the fifth most important disease affecting human health (1). With the development of the world economy and changes in dietary structure, high-calorie foods are becoming more and more popular among young people, leading to a significant increase in the obesity rate of young people worldwide (2,3). Obesity is an important cause of chronic non-communicable diseases; adolescent obesity is not only accompanied by a decline in cardiorespiratory endurance, but also closely related to the occurrence of cardiovascular and metabolic diseases in adulthood (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%